2014
DOI: 10.1039/c4sm00169a
|View full text |Cite
|
Sign up to set email alerts
|

Organization of microbeads in Leidenfrost drops

Abstract: We investigated the organization of micrometric hydrophilic beads (glass or basalt) immersed in Leidenfrost drops. Starting from a large volume of water compared to the volume of the beads, while the liquid evaporates, we observed that the grains are eventually trapped at the interface of the droplet and accumulate. At a moment, the grains entirely cover the droplet. We measured the surface area at this moment as a function of the total mass of particles inserted in the droplet. We concluded that the grains fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Using a low pressure environment, Celestini et al [21] found that the Leidenfrost droplets of water can be generated at room temperature. In addition, Celestini and Kirstetter [22] have investigated the influence of an electric field on Leidenfrost droplets and Maquet et al [23] have studied the organization of microbeads in Leidenfrost droplets. Most recently, Wells et al…”
Section: Introductionmentioning
confidence: 99%
“…Using a low pressure environment, Celestini et al [21] found that the Leidenfrost droplets of water can be generated at room temperature. In addition, Celestini and Kirstetter [22] have investigated the influence of an electric field on Leidenfrost droplets and Maquet et al [23] have studied the organization of microbeads in Leidenfrost droplets. Most recently, Wells et al…”
Section: Introductionmentioning
confidence: 99%
“…To obtain such liquid marbles, one can use hydrophobic grains (Aussilous and Quéré, 2001). In the present case, however, we considered glass beads and basalt beads which are both hydrophilic materials (Maquet et al, 2014). The grains fully covered the droplet thermally insulating the droplet from the plate.…”
Section: Water 1 Microparticlementioning
confidence: 99%
“…As a result, the assembly process demonstrates a facile fabrication strategy to create a monolayer of microlenses encapsulating a liquid marble without an extra process, such as a cleaning 38 or evaporation. 39 We then rely on the mobility of liquid marbles under shear to create arrays of compound lenses. Finally, we polymerize the lenses to arrest the assembled structure and form a mechanically robust hierarchical material.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The formation of a monolayer of microlenses with the same refractive index as the droplet leads to first demonstration of liquid marbles that function as compound lenses. As a result, the assembly process demonstrates a facile fabrication strategy to create a monolayer of microlenses encapsulating a liquid marble without an extra process, such as a cleaning or evaporation . We then rely on the mobility of liquid marbles under shear to create arrays of compound lenses.…”
Section: Introductionmentioning
confidence: 99%